From the collection Chinese People's Movement. See the inventory, Call number PUB K 14, PUB K 16, PUB K 29. . Slides of demonstrations on Tiananmen-square
From the collection Chinese People's Movement. See the inventory, Call number PUB K 14, PUB K 16, PUB K 29. Slides of demonstrations on Tiananmen-square.